Developing Teachers’ Intercultural Competences Through International Mobility Programmes - Kastelic , Manca; Bratož, Silva; Pirih, Anja (Revija za elementarno izobraževanje, 2024)
The main aim of the paper is to explore primary school teachers’ attitudes towards the impact of international mobility on their professional and personal development, with a special focus on the ways mobility contributed to the development of their intercultural competences. We present the results of a qualitative study based on semi-structured interviews with teachers (n=10) who have taken part in Erasmus+ mobility abroad. The results of the study show that the experience of mobility proved to be a positive one for all interviewees who reported numerous benefits in terms of professional and personal development of the participants as well as in terms of gaining intercultural competences.
Keywords: international mobility, intercultural competence, professional development, primary school teachers.